Problématique d’élaboration des prévisions des matières du cours d’histoire dans les écoles secondaires d’Isangi-centre et de ses environs. Cas des enseignants des classes de troisièmes et quatrièmes secondaires - Bokwala , Jean-Pierre Basenda Bokwala; John Loela Geutu (IJRDO- Journal of Educational Research, 2020)
In secondary schools of Isangi –center and its immediate environs, the teachers of history course, those giving lesson in the third (3rd ) and fourth (4th) form in particular, don’t plan the previsions of the matters. The notice NO DEPSP/C.C.E/001/84/00764/85 of March 27, 1985 orders very firmly the getting hold of pedagogical documents, and then it is giving more exact detail saying than the prevision of matter is work hand book that helps the teacher not to acheive quick his his course or not to harry his teaching at the end of the year to end the shedule. The reason why a clear and detailed explanation of his gender to show the difficulties encountered by the teacher to plan the prevision of matters based on Didactic support miss: national schedule, agreed book and conform to the pattern, school calendar and civils calendars Very great matter contents in history 3 et 4 Insuficient weekly time table, that is twice a week At last, theoritical notions miss in calculation of the numbers of working days, the courses, and the real hours of courses in relationships with the total number of the lesson to teach during the whole of the school year.